Respuestas

2013-05-02T02:08:24+02:00

1) 6x-6+3x=3x+6 

   9x - 6 = 3x + 6

 9x - 3x  - 6 = 6

6x - 6 = 6

6x = 6+ 6

6x = 12

x = 12/6

x = 2

 

 

2)3x+5x-49=2x+x+11

  8x - 49 = 3x + 11

  8x - 3x - 49 = 11

      5x - 49 = 11

       5x = 11 + 49

      5x = 60

       x  = 60/5

      x = 12

 

Saludos.

2013-05-02T02:09:52+02:00

   6x-6+3x=3x+6

 6x+3x-3x=6+6

           6x=12

            x=12/6

            x=2

 

   3x+5x-49=2x+x+11

3x+5x-2x-x=11+49

               5x=60

                 x=60/5

                x=12

 

Espero te sirva :D